Decomposing US regional income inequality from 1969 to 2009. Issue 11 (23rd July 2016) - Doran, Justin; Jordan, Declan
ABSTRACT: This article analyses changes in levels and composition of income inequality among US counties from 1969 to 2009. It also decomposes inequality using the Theil coefficient into between-State and within-State inequality. The article finds that income inequality has increased in the period studied with between-State inequality decreasing and within-State inequality increasing. We subsequently decompose income inequality into the proportion arising from differences in productivity and employment–population ratios across counties. The results suggest that inequality arising from differentials in labour productivity has fallen over the period studied while those arising from employment–population ratio differences have increased.